2022
DOI: 10.3389/fphar.2021.785371
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Allergic Properties of Propolis: Evidence From Preclinical and Clinical Studies

Abstract: Allergic diseases are a global health burden with increasing prevalence. Side effects of available medications (antihistamines and steroids), lack of patients’ perceived effectiveness and high cost of biologic therapies (omalizumab) are challenges to the clinical management of allergic diseases. As allergy symptoms persist for a long time, complementary and alternative medicine (CAM) such as propolis may be considered a potential prophylactic or therapeutic option to avoid long-term medication use. Propolis is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…In fact, Brazilian propolis has been shown to exert anti-allergic properties due to inhibitory effects on the activation of mast cells and basophils. Preclinical studies demonstrated the effects of propolis extracts against allergic symptoms, such as inflammation, asthma, rhinitis, atopic dermatitis, and food allergy, most studies having been carried out with Brazilian green propolis [ 113 ]. It remains to be determined which components of propolis account for the anti-allergic activity.…”
Section: Safety: Current Pharmaceutical Drugs Vs Propolismentioning
confidence: 99%
“…In fact, Brazilian propolis has been shown to exert anti-allergic properties due to inhibitory effects on the activation of mast cells and basophils. Preclinical studies demonstrated the effects of propolis extracts against allergic symptoms, such as inflammation, asthma, rhinitis, atopic dermatitis, and food allergy, most studies having been carried out with Brazilian green propolis [ 113 ]. It remains to be determined which components of propolis account for the anti-allergic activity.…”
Section: Safety: Current Pharmaceutical Drugs Vs Propolismentioning
confidence: 99%
“…Some of them also work in a spasmogenic way or activate respiratory burst and degranulation of leukocytes [ 54 , 55 , 56 , 69 , 70 , 71 , 72 ]. Thus, lipoxygenase plays a decisive role in pathological processes, such as inflammation or allergies [ 54 , 55 , 56 , 70 , 71 , 125 , 126 ]. Moreover, certain enzymatic products of lipoxygenases are thought to be essential for tumorigenesis [ 65 ].…”
Section: Role Of Propolis and Its Components In Allergymentioning
confidence: 99%
“…Therefore, hydroxylated resveratrol analogues represent a novel class of highly selective COX-2 inhibitors and promising candidates for in vivo studies. Furthermore, promising in vitro data indicated that treatment with selective COX-2 inhibitors such as curcumin, chlorogenic acid, CA, resveratrol, galangin or the flavonoid silymarin may reduce the risk of Alzheimer’s, and Parkinson’s disease [ 142 , 143 ] and also be effective in the treatment of asthma and other allergic diseases [ 125 , 136 , 144 , 145 ].…”
Section: Role Of Propolis and Its Components In Allergymentioning
confidence: 99%
See 2 more Smart Citations